2021
DOI: 10.1007/s10639-021-10678-x
|View full text |Cite
|
Sign up to set email alerts
|

Remote learning during COVID-19: cognitive appraisals and perceptions of english medium of instruction (EMI) students

Abstract: Many countries responded to the Covid-19 pandemic by transforming all face-toface (F2F) courses to emergency remote teaching with a sudden decision. This rapid shift was unexpected and staggering for the university students. The purpose of the present study is to explore how students studying in English Medium Instructed (EMI) programs cognitively appraised the transformation from F2F to online learning, and to examine if there is any relation between perceived self-efficacy in academic second language (L2) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…Independent variable. Motivation was measured through a measurement scale of five items developed by Yeh (2014). This scale was recently developed and used in Taiwan, a research context that has many similarities to Vietnam.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Independent variable. Motivation was measured through a measurement scale of five items developed by Yeh (2014). This scale was recently developed and used in Taiwan, a research context that has many similarities to Vietnam.…”
Section: Methodsmentioning
confidence: 99%
“…Tsui and Ngo (2017) claimed that both learning English for a career and for internationalization have positive effects on students' satisfaction with their university. Karakas (2017) found that the majority of Turkish students were satisfied with EMI in general, the four components of teaching, content instructors' English, their institutions, and their institutions' policies and procedures regarding English language use and instruction while (Yüksel, 2022) discovered that the perceived level of interactional quality and satisfaction had a strong positive correlation. Kim and Yoon (2018) examined the reactions of Korean students to EMI in the field of science and engineering.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, L2-speaking faculty at CEU and elsewhere adopted new communication strategies fitting the online environment. They looked for efficient words to motivate seemingly disengaged students and produced greater amounts of complex written text (Cicillini and Giacosa, 2020;Pun and Thomas, 2020;Yüksel, 2022). Furthermore, instructors had to swiftly improve not only their fluency in the language of instruction but also in the "language" of hardware, software, and their uses in teaching (Kohnke and Jarvis, 2021).…”
Section: The Pandemic In Other Tongues: English and Technology As Med...mentioning
confidence: 99%
“…Nevertheless, the author believes that the students’ perceptions and feelings have been left aside in all these hassles. The transition from face-to-face to drastic online teaching can be said to have a mental impact on tertiary level students (Yüksel, 2022) as they are left on their own to manage both their personal and educational lives. Therefore, it becomes very important to understand the online teaching and learning components from a student’s perspective.…”
Section: Introductionmentioning
confidence: 99%